Mother and Mother Earth in the Era of Oil Palm Plantations: Ecological Feminism Study in Tebo Regency - Ramona, Elza; Angraini, Peppy (PALASTREN: Jurnal Studi Gender, 2024)
This article aims to describe the impacts caused by the land conversion that occurred in Tebo Regency from rubber plantations to oil palm plantations. Ecological Feminism is used as an analytical tool to see how women are marginalized from nature and how the opening of oil palm plantations has an impact on ecological diversity and women's lives. In this research, a descriptive-analytical qualitative method was used where data collection was carried out by observing and exploring literature related to the impact of oil palm plantations, women's poverty, and women's relationship with nature. The findings in this research are that women are marginalized from nature, nature from nature, and women from economic access by the conversion of land from rubber plantations to oil palm plantations. The marginalization of women in accessing land, returns them to the domestic sphere. This also causes environmental damage to get worse, so that directly or indirectly it is a form of empowerment of women. They have difficulty obtaining fuel/firewood, clean water, and diversity is reduced .